(3Gdefgd GdYPH GdQhi aj JQLeI bWH GdChdjGA Gdfhhis - (3GdSNGhj , TeS GdOjf eMeO Hf YHO GdQMef Hf eMeO GdSNGhj, GdSNGhj,J (B902 (3g` s
(3ChdgG (B:s
(3hHYO agPG LRA GSJhajJ ajg CMhGd TjN GdGSdGe eMj GdOjf Gdfhhi s
(3BNQgG (B:s
(3aQMe Gddg KQGg hHQO eVLYg hQVi Gddg Yfg Efg Ydi cd TF bOjQ s
(3hQO GdYfhGf gcPG ceG SeGg GdeDda ai JQLeJg dfaSg ai GdVhA GdGeY (B"8 : 17"s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B194 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B150s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B680 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B306 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
Keywords: (3GdJGQjNs